Response of Wheat Plants to Combinations of Herbicides with Insecticides and Fungicides - VIECELLI,M. (2019)
ABSTRACT: The combination of herbicides and other pesticides can influence weed and crop management. This study aimed to evaluate the response of the combination of different herbicides with insecticides or fungicides of different chemical groups on the development and yield of wheat grains of the cultivar ORS Vintecinco. The experimental design was a randomized block design with three replications. The experiment consisted of 33 treatments, as follows: control without application and application of the herbicides 2,4-D (1,005 g a.e. ha-1), bentazon (756 g a.i. ha-1), metsulfuron-methyl (3 g a.i. ha-1), and pyroxsulam (16 g a.i. ha-1), isolated or combined with the insecticides chlorfluazuron (15 g a.i. ha-1), chlorpyrifos (720 g a.i. ha-1), deltamethrin (5 g a.i. ha-1), and methomyl (5 g a.i. ha-1) or with the fungicides azoxystrobin (100 g a.i. ha-1), carbendazim (250 g a.i. ha-1), and propiconazole (190 g a.i. ha-1). Relative tolerance (RT), shoot dry matter (SDM), yield components, and grain yield were evaluated. In general, pyroxsulam had the highest number of synergistic interactions with insecticides and fungicides, reducing RT and SDM, especially the combination pyroxsulam + chlorpyrifos due to a lower RT level (45%) and higher SDM reduction (52%). All combinations of herbicides with the insecticide chlorpyrifos and most of the combinations with the fungicide propiconazole led to a reduction of grain yield when compared to their isolated application or to control without application.